Open shortest path first (OSPF) routing protocol simulation. - Sidhu, Deepinder
Open Shortest Path First (OSPF) is a dynamic, hierarchical routing protocol designed to support routing in TCP/IP networks. A simulation of the OSPF Election Protocol shows three results: (1) The Designated Router (DR) can be elected in constant time. (2) If a router has a limited number of input buffers, a competition for buffers between the Election and the Flooding Protocols increases the election time and causes an oscillatory behavior.At each router, the Router-ID of the DR continuously changes causing instability. (3) In the worst case, when the DR and the BDR fail at the same time, the DR-agreement-time is bounded above by twice the HelloInterval. A simulation of the OSPF Flooding Protocol, using 20, 50 and 80 router point-to-point networks, shows three results: (1) For the 50 router network, as link speed exceeds 4000 Kbps, the probability of overflowing the input buffers increases causing retransmissions. The increase in bootup-convergence-time from retransmissions is bounded by two and three times the RxmtInterval for link speeds of 4000 to 6000 Kbps and above 50 Mbps respectively. The increase in the bootup-convergence-time is due to large number of unacknowledged flooding packets received within RxmtInterval. (2) For 20 and 50 router networks, the input buffer size has little impact on the bootup-convergence-time. For the 80 router network, a small change in the input buffer size drastically changes the bootup-convergence-time. (3) Reducing the value of the RxmtInterval lowers the bootup-convergence-time at high link speeds.
Keywords: Computer systems organization; Computer communication networks; Network protocols; TCP IP; Network architecture and design; Network topology; Theory of computation; Analysis of algorithms and problem complexity; Nonnumerical algorithms and problems; Routing and layout; Mathematics of computing; Discrete mathematics; Graph theory; Trees; Path and circuit problems; Computing methodologies; Simulation and modeling; Types of simulation; Discrete event; Algorithms; Design; Performance; Reliability